"Od splinu na barykady". Romantyczna biografia Rudolfa von Gerolstein = "Passing from spleen to barricades". Rudolf von Gerolstein`s Romantic Biography - Sokołowicz, Małgorzata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
"The Mysteries of Paris" by Eugene Sue was an exceptionally popular newspaper serial, which continued to hold the breath of French people between 1842 and 1843. The public immediately took to its main protagonist, Rudolf von Gerolstein, a wealthy prince wandering the darkest and gloomiest districts of Paris, helping the poor and punishing the cruel.
Keywords: Sue, Eugene (pseud.), Sue, Marie-Joseph (1804-1857); literatura francuska - historia - 19 w.; powieść francuska - 19 w.